Long-term outcomes of radiofrequency ablation combined with hepatectomy compared with hepatectomy alone for colorectal liver metastases. Issue 5 (23rd January 2017) - Imai, K; Allard, M-A; Castro Benitez, C; Vibert, E; Sa Cunha, A; Cherqui, D; Castaing, D; Baba, H; Adam, R
Abstract: Background: Combining radiofrequency ablation (RFA) with hepatectomy may enable treatment with curative intent for patients with colorectal liver metastasis (CRLM). However, the oncological outcomes in comparison with resection alone remain to be clarified. Methods: Patients who underwent a first hepatectomy between 2001 and 2012 for CRLM were enrolled. Short- and long-term outcomes of patients who underwent hepatectomy plus RFA were compared with those of patients who had hepatectomy alone using propensity score matching. Results: Of a total of 553 patients, hepatectomy + RFA and hepatectomy alone were performed in 37 and 516 respectively. Before matching, patients in the hepatectomy + RFA group were characterized primarily by a larger tumour burden. After matching of 31 patients who underwent hepatectomy + RFA with 93 who had hepatectomy alone, background characteristics were well balanced. In the matched cohort, overall and disease-free survival in the hepatectomy + RFA group were no different from those among patients who had hepatectomy alone (5-year overall survival rate 57 versus 61 per cent, P = 0·649; 5-year disease-free survival rate 19 versus 17 per cent, P = 0·865). Local recurrence at the ablated site was observed in four of 31 patients (13 per cent). Although overall local recurrence (ablated site and/or cut surface) was more frequent in the hepatectomy + RFA group (9 of 31 (29 per cent) versus 11 of 93 (12 per cent); P = 0·032), there was no difference in intrahepatic disease-free survival between the two groups ( P = 0·705). Conclusion: Hepatectomy + RFA achieved outcomes comparable to hepatectomy alone. Combining RFA with hepatectomy should be considered as an option to achieve cure. Abstract : Ablation plus resection just as good